Sense of life, existential psychotherapy and COVID-19 - Voloshyna, Larysa; Leko, Bohdan; Kushnir, Leonid (Psychosomatic Medicine and General Practice, 2020)
In the modern theory and practice of consulting the search for the meaning of life, prevention, and treatment ("intellectual vaccination"), the existential direction is not represented at all, although its need is obvious and has the right to life. Existential crises can be based on death, serious illness, transitional periods - positive and negative in personal life and professional activity, making irreversible decisions, sudden isolation, searching for the meaning of life, and all this, which is already becoming, we hope, a temporary basis - this is COVID 19. The main content of existentialism testifies that it is indeed one of the most worldly, personality-oriented directions of modern psychological science, which seeks to explain the essence of man in indissoluble unity with all the structures of its existence. Existential psychotherapy - psychological assistance based on the mind, respect, and active knowledge of the therapist of all the features and aspects of the individual being (existence) of the patient’s personality, without the intention to find out the pathological or ineffective characteristics of his life, behavior, and activity. The humanistic potential is significant, which affirms a person as a self-sufficient person. The authors gave examples of the application of the method of existential psychotherapy in the rehabilitation of patients with postcovid syndrome and other pathological conditions. Analyzing the thoughts and actions of our patients, we have in practice received confirmation of the scientific works of scientists dealing with the problem under study. Promising areas can also be considered the creation of the school "Existential psychotherapy in the rehabilitation of patients with post-coid syndrome", the holding of a conference on the topic "Existential psychotherapy in the development and rehabilitation of recovering from COVID-19", the opening of a "humanitarian vaccination room" and others. Taking into account modern trends in society, existential psychotherapy has a great future in the cognitive, therapeutic areas, as well as in the rehabilitation of sick and post-sighted convalescents. Separately, it should be noted that all the data they use in this article is given taking into account the time frame until February 14, 2021.